Characteristics of the Approximate-Optimal Training Indicators of Goalkeepers in Modern Football - Igor Doroshenko; Andrii Svatyev; Valerij Shamardin; Bogdan Khorkavyy; Daria Vaniuk; Eduard Doroshenko (Journal of Learning Theory and Methodology)
Objectives. Is to systematize data on determining approximate and optimal indicators of training activities of goalkeepers in football at different stages of sports improvement in order to improve their training.